DIRECT OXIDATION OF EUGENOL USING A PERMANGANATE - Reinner Ishaq Lerrick (Molekul, 2009)
Direct oxidation of eugenol has been done using potassium permanganate. This research attempts to produce benzyl carboxylic acid, an important intermediate reactant for isoflavone synthesis, directly by breaking the p bond of allillic group attached to eugenol. The oxidation procedures were adopted from Wahyuningsih and Kusumaningsih anetol oxidation reactions. There were three modifications done i.e. one polar system of the oxidation environment, variation of time of reflux and temperature. Eugenol was firstly diluted in water by converting to its salt type and then oxidized using KMnO4 at 75 oC for 4 hours. The expected acid was separated by acidifying using sulfuric acid.The result showed that direct oxidation of eugenol using modified method of Wahyuningsih gave only a vicinal diol which undergoes polymerization into product in 80% yield with 83% purity. However, variation of time of reflux of Wahyuningsih method showed the same result with Kusumaningsih method as brown oily viscous liquid. The product was only 38% purity.